2022
DOI: 10.1007/s10570-022-04898-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis by carbonate aminolysis and chiral recognition ability of cellulose 2,3-bis(3,5-dimethylphenyl carbamate)-6-(α-phenylethyl carbamate) selectors

Abstract: Novel chiral selectors based on cellulose 2,3-bis(3,5-dimethylphenyl carbamate)-6-(α-phenylethyl carbamate) were regioselectively synthesized by carbonate aminolysis and isocyanate chemistry. By oxycarbonylation with phenyl chloroformate, carbamoylation with 3,5-dimethylphenyl isocyanate, and subsequent aminolysis of the previously introduced reactive carbonate moiety at C6 with enantiopure (R)-or (S)-α-phenylethylamine, chiral selectors have been obtained, which regioselectively carry two different phenyl car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…Further studies with smaller silica particles and higher surface areas, allowing higher efficiencies and consequently higher selector loadings with higher retention and selectivity, are ongoing. A previous comparison from our work (Bui et al 2022b) with coated materials carrying 20 wt% of selector has shown that the overall performance matched that of commercial reference materials. However, with the present silica dimensions (i.e., relatively low surface area), it was not possible to achieve such high selector loadings (vide supra).…”
Section: Enantioseparation Evaluationsupporting
confidence: 60%
See 1 more Smart Citation
“…Further studies with smaller silica particles and higher surface areas, allowing higher efficiencies and consequently higher selector loadings with higher retention and selectivity, are ongoing. A previous comparison from our work (Bui et al 2022b) with coated materials carrying 20 wt% of selector has shown that the overall performance matched that of commercial reference materials. However, with the present silica dimensions (i.e., relatively low surface area), it was not possible to achieve such high selector loadings (vide supra).…”
Section: Enantioseparation Evaluationsupporting
confidence: 60%
“…The higher reactivity and selectivity of phenyl chloroformate towards C6-OH versus C2-OH and C3-OH have already been reported (Elschner et al 2014;Ganske and Heinze 2018). In a previous study, we have optimized the protocol towards quantitative oxycarbonylation of C6-OH (Bui et al 2022b) and also reported on the optimization and successful aminolysis reaction between the polysaccharidic carbonates (Bui et al 2022a). The obtained phenyl carbonate served as a reactive intermediate for subsequent aminolysis with propargylamine yielding a propynyl carbamate moiety as an alkyne donor for immobilization of the CS onto 3-azidopropyl-functionalized silica gel (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…2, the EA results of all reported cellulose derivatives are summarized in Table 1. The FTIR and solid-state 13 C NMR spectra of cellulose derivative 1 were in full agreement with literature data (Liu et al 2013;Wei et al 2019;Bui et al 2022a;Bui et al 2022b). Cellulose derivative 1 is a well-known CS in chiral HPLC column materials and has been commercialized by several companies.…”
Section: Cellulose Tris(35-dimethylphenyl Carbamate)supporting
confidence: 84%
“…Previously published procedures were adapted to synthesize 3-aminopropyl-functionalized silica gel (APS) as an inert carrier for the CSs (Engelhardt and Orth 1987;Yashima et al 1996;Okada et al 2016;Bui et al 2022a). Silica gel (10 g) was immersed in toluene (200 mL) during mechanical stirring, and the mixture was dried by azeotropic distillation in a dry nitrogen atmosphere.…”
Section: Synthesis Of 3-aminopropyl-functionalized Silica Gel Apsmentioning
confidence: 99%
See 1 more Smart Citation